IMPLEMENTASI ACTIVE DIRECTORY DOMAIN SERVICES WINDOWS SERVER 2012 MENGGUNAKAN VIRTUALISASI HYPERVISOR VMWARE ESXI (STUDY KASUS PT E-TRANS) - Handri Kusuma; Mochamad Adhari Adiguna (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
This study aims to determine the implementation of Active Directory Domain Services Windows Server 2012 Using VMware ESXi Hypervisor Virtualization in the Case Study of PT E-Trans. Research shows that there are two specifications, namely the first software specifications consisting of Operating System, Hypervisor and OS Virtual Machine, the second hardware specifications consisting of ram, hdd, processor and other devices such as the internet, the results of the study show VMware can be used as a means to utilize virtualization methods to optimize its Management Server and reduce inventory costs, then VMware is useful for increasing and decreasing the number of server computers or virtual machines that can support many applications, Active Directory Domain Services on Windows Server 2012 provided efficient benefits and integration for enterprise network management and enhanced security.